Answer:
![(x-4)^2+(y-5)^2=49](https://tex.z-dn.net/?f=%28x-4%29%5E2%2B%28y-5%29%5E2%3D49)
Step-by-step explanation:
So we want to find the equation of a circle with the center at (4,5) and which passes through the point (-3,5).
First, recall the standard form for a circle, given by the equation:
![(x-h)^2+(y-k)^2=r^2](https://tex.z-dn.net/?f=%28x-h%29%5E2%2B%28y-k%29%5E2%3Dr%5E2)
Where (h,k) is the center and r is the radius.
We already know that the center is (4,5). So, substitute 4 for h and 5 for k. Therefore, our equation is now:
![(x-4)^2+(y-5)^2=r^2](https://tex.z-dn.net/?f=%28x-4%29%5E2%2B%28y-5%29%5E2%3Dr%5E2)
Now, we need to find the radius.
Remember that our circle passes through the point (-3,5). In other words, when x is -3, y is 5. So, substitute -3 for x and 5 for y to solve for r. Therefore:
![(-3-4)^2+(5-5)^2=r^2](https://tex.z-dn.net/?f=%28-3-4%29%5E2%2B%285-5%29%5E2%3Dr%5E2)
Subtract within the parentheses:
![(-7)^2+(0)^2=r^2](https://tex.z-dn.net/?f=%28-7%29%5E2%2B%280%29%5E2%3Dr%5E2)
Square:
![49=r^2](https://tex.z-dn.net/?f=49%3Dr%5E2)
Square root:
![r=7](https://tex.z-dn.net/?f=r%3D7)
Therefore, the radius is 7.
So, substitute 7 into our equation, we will acquire:
![(x-4)^2+(y-5)^2=(7)^2](https://tex.z-dn.net/?f=%28x-4%29%5E2%2B%28y-5%29%5E2%3D%287%29%5E2)
Square:
![(x-4)^2+(y-5)^2=49](https://tex.z-dn.net/?f=%28x-4%29%5E2%2B%28y-5%29%5E2%3D49)
So, our equation is:
![(x-4)^2+(y-5)^2=49](https://tex.z-dn.net/?f=%28x-4%29%5E2%2B%28y-5%29%5E2%3D49)
And we're done!